Family literacy programmes and young children's language and literacy development: paying attention to families' home language. Issue 3 (3rd April 2017) - Anderson, Jim; Anderson, Ann; Sadiq, Assadullah
ABSTRACT: In this article, we review the literature on the impact of family literacy programmes on young children's language and literacy learning. After defining family literacy, we present a brief historical overview of family literacy programmes, including persistent questions regarding their effectiveness with respect to young children's language and literacy learning and their propensity to promote the dominant language (e.g. English) while ignoring the benefits of bilingualism and of families' home language maintenance. Meta-analyses reveal that family literacy programmes have a positive effect on young children's language and learning development and studies of bilingual family literacy programmes indicate that they are effective in significantly increasing children's early literacy knowledge in the dominant or mainstream language and in promoting home language maintenance. This finding lends empirical support for bilingual family literacy programmes and the concept of additive bilingualism. We conclude by suggesting implications for practice and for future research.